Associations between oxidative balance scores and heart failure among americans: NHANES (2007–2018) - Xiaozhuo Xu; Xueli Wang; Xu Han (BMC Cardiovascular Disorders)
Abstract Background The relationship between oxidative balance score (OBS) and heart failure (HF) is controversial. The OBS was used to assess systemic oxidative stress status, with higher OBS scores implying exposure to more antioxidants. This study aimed to explore whether OBS is associated with heart failure in US adults. Methods A cross-sectional investigation was carried out using information from the National Health and Nutrition Examination Survey 2007–2018. The linear link between OBS and HF in adults aged ≥ 45 years was investigated using multivariate linear regression models. Interaction tests and subgroup analysis were also conducted. Results The prevalence of HF was 3.84%. There was a significant negative relationship between OBS (OR: 0.96 ,95%CI: 0.95–0.98, P < 0.0001) and HF. In the fully adjusted model, compared to the lowest quartile of OBS, subjects in the highest quartile had a 45% lower likelihood of developing HF (OR: 0.55, 95% CI: 0.41–0.74, p < 0.0001). In stratified analysis, OBS and HF showed no obvious negative correlation. Conclusion OBS was strongly negatively associated with heart failure. The findings underline the significance of adhering to an antioxidant diet and lifestyle, which helps prevent heart failure.